Planetary wave coupling (5–6-day waves) in the low-latitude atmosphere–ionosphere system - Pancheva, D.V.; Mukhtarov, P.J.; Mitchell, N.J.; Fritts, D.C.; Riggin, D.M.; Takahashi, H.; Batista, P.P.; Clemesha, B.R.; Gurubaran, S.; Ramkumar, G. (My University, 2008)
Vertical coupling in the low-latitude atmosphere–ionosphere system driven by the 5-day Rossby W1 and 6-day Kelvin E1 waves in the low-latitude MLT region has been investigated. Three different types of data were analysed in order to detect and extract the ∼6-day wave signals. The National Centres for Environmental Prediction (NCEP) geopotential height and zonal wind data at two pressure levels, 30 and 10 hPa, were used to explore the features of the ∼6-day waves present in the stratosphere during the period from 1 July to 31 December 2004. The ∼6-day wave activity was identified in the neutral MLT winds by radar measurements located at four equatorial and three tropical stations. The ∼6-day variations in the ionospheric electric currents (registered by perturbations in the geomagnetic field) were detected in the data from 26 magnetometer stations situated at low latitudes. The analysis shows that the global ∼6-day Kelvin E1 and ∼6-day Rossby W1 waves observed in the low-latitude MLT region are most probably vertically propagating from the stratosphere. The global ∼6-day W1 and E1 waves seen in the ionospheric electric currents are caused by the simultaneous ∼6-day wave activity in the MLT region. The main forcing agent in the equatorial MLT region seems to be the waves themselves, whereas in the tropical MLT region the modulated tides are also of importance.
Keywords: Kelvin waves; 5-day normal mode; Modulated tides; Dynamo electric currents; Planetary wave coupling; MLT region